Country Level Sales of Ultra-Processed Foods and Sugar-Sweetened Beverages Predict Higher BMI and Increased Prevalence of Overweight in Adult and Youth Populations. (29th May 2020) - Eaton, Jacob
Abstract: Objectives: Ultra-processed foods (UPF) and sugar-sweetened beverages (SSB) comprise over 50% of energy intake in most upper-middle and high-income contexts. Higher intake of UPF and SSB is associated with an increased prevalence of overweight and obesity at the individual level, but few studies have examined the association between UPF, SSB, and BMI at the country level. The objective of this study was to evaluate global trends in UPF and SSB sales and associations with trajectories of change in BMI and prevalence of overweight, and obesity. Methods: Data on UPF and SSB sales was collected from EuroMonitor International; BMI, overweight, and obesity prevalence from the NCD Risk Factor Collaboration; and potential confounders from the World Health Organization Global Health Observatory. Longitudinal multi-level models were used to estimate the relationship between country-level UPF/SSB sales and weight trajectories for adults and children and adolescents less than 19 years, for both general population and sex disaggregated. Results: UPF sales grew 2.7% between 2005 and 2018. Sales were highest in high income contexts of North America (139.3 kg/person/year) and Europe (117.3 kg/p/y) but grew most rapidly in low and lower-middle income countries, particularly South Asia and Sub-Saharan Africa. SSB sales grew 1.9% but ranged from −22.4% in North America (120.3 liters/person/year in 2018) to 144.7% in South Asia (7.3 liters/p/year). Both UPF and SSB were significant and positive predictors of BMI; 1 SD increases in sales predicted mean population BMI increases between 0.2 kg/m² and 0.5 kg/m². Neither UPF nor SSB predicted obesity, but both were significantly associated with overweight prevalence trajectories for the adult general population and for males. Associations remained controlling for both country calorie supply and physical inactivity prevalence. In children and adolescents (5–19 years), SSBs significantly predicted BMI levels and obesity prevalence, while only UPF was associated with overweight. Conclusions: UPF and SSB sales have a significant impact on country-level BMI trajectories. At current rates, upper-middle income countries will soon equal high-income contexts in UPF/SSB consumption and BMI trajectories. Findings suggest the need for global level action to limit UPF and SSB consumption. Funding Sources: No funding sources declared.